Asuhan Keperawatan Pada Pasien Acute Lung Oedem (ALO) Dengan Intervensi Penghisapan Jalan Napas Dan Pengempesan Balon ETT / Cuff Terhadap Pencegahan Penumpukan Sekret Di Ruang ICU RSUD Kabupaten Tangerang - Fauzi Iskandar; Zahrah Maulidia Septimar; Andi Setiyawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Acute Lung Oedema (ALO) is an emergency condition that requires immediate action and has fatal and more dangerous consequences which will disrupt the gas exchange process in the alveoli due to the alveoli being filled with fluid. Based on the results of the initial survey in the ICU room at Tangerang Regional Hospital, it was found that the number of ICU patients with cases of pulmonary edema or ALO in 2023 was 14 people and from June to January 2024 there were 14 people. Nursing actions as an evidence base that can be provided include sucking mucus for less than 15 seconds and emptying the ETT cuff periodically. This implementation can increase airway clearance, thereby preventing accumulation of secretions that can cause aspiration. Proving the theory through providing nursing care carried out 5x with results showing that providing mucus suction in less than 15 seconds, and emptying the ETT cuff periodically, can improve the airway clearance status as indicated by a decrease in sputum production, color and consistency. Method: This writing method uses patient intervention and observation carried out for five days, to determine the patient's condition and provide appropriate nursing care which is then documented. Results: Based on the results of the monitoring carried out, it can be concluded that there are differences in the conditions of secretion production before and after the suction intervention was carried out by deflating the ETT (Cuff) balloon for 5-15 seconds. With the results criteria, secretion production is reduced. Conclusion: for patients with thick and purulent secretions, suction by deflating the ETT balloon (Cuff) becomes more effective and secretion production decreases. Nursing actions as an evidence base that can be given include sucking mucus for less than 15 seconds and emptying the ETT cuff periodically.